Skip to content

Instantly share code, notes, and snippets.

Embed
What would you like to do?
Demonstration of incorrect (Enum x, Enum y) => Enum (x, y) instance
-- See http://stackoverflow.com/questions/9967790/instance-in-haskell
instance (Enum x, Enum y) => Enum (x, y) where
fromEnum (x,y) =
k^2 + 2*j + if permuted then 1 else 0
where
k = max (fromEnum x) (fromEnum y)
j = min (fromEnum x) (fromEnum y)
permuted = (fromEnum y) > (fromEnum x)
toEnum n =
let k = floor . sqrt $ fromIntegral n
(j, permdAdd) = (n-k) `divMod` 2
permute (x,y) | permdAdd>0 = (toEnum y, toEnum x)
| otherwise = (toEnum x, toEnum y)
in permute (k, j)
data A = A1 | A2 deriving (Show, Enum)
data B = B1 | B2 | B3 deriving (Show, Enum)
main = do
print [(A1,A1)..(A2,A2)]
print [(B1,B1)..(B3,B3)]
print [(A1,B1)..(A2,B3)]
print [(B1,A1)..(B3,A2)]
-- Program crashes, as expected, since creating such an instance is impossible.
Sign up for free to join this conversation on GitHub. Already have an account? Sign in to comment
You can’t perform that action at this time.